Analyzing the Influence of Social Media Content on Online Purchase Decisions: A Case Study from Saudi Arabia Electronic Products Market - Hasanin, Tawfiq; Jambi, Sahar; Alrashidi, Meshal (International Review of Management and Marketing, 2025)
This study aims primarily to analyze the quality of the online electronic product Purchase Decision-Making Process from the perspective of provided content type through social media in the Kingdom of Saudi Arabia. This study focused on four variables regarding the purchase decision-making process, which are need recognition, information gathering, alternatives evaluation, and making the purchase decision, to examine the differences for each of them across three main groups of provided content via social media: Visual/audio content, textual content and images content. The proposed research is designed based on a quantitative method utilizing a questionnaire survey with a sample size of 508 online respondents. The results showed that there is a somewhat decline in analyzing the quality of the online electronic product Purchase Decision-Making Process in the Kingdom. This process also differs across content type groups in favor of image content compared to visual/audio content and textual content with regard to the variables of gathering information, evaluating alternatives, and purchasing decisions. The implications can be described and explained in more detail, corresponding to the research questions and objectives of this study.